478 Enhancing Technology Interface in the Dissection Room (DR). (19th August 2022) - Balfour, J; Banziger, C; Burr, P; Quigley, C; Chisholm, F
Abstract: Aim: Anatomy teaching increasingly utilises technology alongside dissection to improve anatomy teaching. Student use of the touchscreen computers in dissection sessions at the University of St. Andrews was infrequent, with students lacking confidence in touchscreen use. The aim of this QI project was to improve medical student confidence and increase the use of touchscreen computers in the DR during dissection sessions. Method: A data-collection tool was designed and tested. It included 4 Likert-style and one blank space question. 111 baseline responses from 3rd-year medical students were collected over 1 week in November 2021. Documentation was optimised for touchscreen usage. Cycle 2 was collected from the same cohort, with 83 responses. The second intervention introduced styluses. Cycle 3, with 85 responses, was collected. Results: Question 1 examined awareness of touchscreen function. Positive responses (agree and strongly agree) increased from 76.5% to 95.2%, then 97.7% after interventions 1 and 2 respectively. Positive responses for question 2, examining confidence, improved from 53.2% to 88.0%, then 96.5%. Positive responses to question 3, examining the frequency of touchscreen use, improved from 49.6% to 91.6% then 92.9%. Positive responses for question 4, examining how useful touchscreens were for student learning, improved from 70.3% to 94.0%, then 97.7%. Blank space questions demonstrated positive opinions of changes made in the dissection room. Conclusions: The significant and sustained increase in positive responses regarding student confidence, touchscreen use and the usefulness of touchscreens as an adjunct to dissection in the DR demonstrated significant improvement in the use of the facilities and student educational experience.